Development of an Effective Model for Particle Size Distribution in Suspension Copolymerization of Styrene/Divinylbenzene - Vivaldo-Lima, Eduardo (My University, 1998)
An effective mathematical model for estimation for the Particle Size Distribution (PSD) in suspension copolymerization of styrene/divinylbenzene has been developed. Its effectiveness is shown as a compromise between a sound theoretical basis and the simplest possible mathematical structure, which makes possible the solution of the governing equations using conventional computational tools. In building the model, a comprehensive and systematic approach was undertaken. The first stage of this approach was to critically review and analyze the literature in suspension polymerization. The most important weaknesses and deficiencies of the existing models and the approaches used to build them were identified, and a strategy to overcome them was designed and implemented. The second stage of the approach was to identify the key factors that control the PSD, and build mechanistic mathematical models of an intermediate and balanced degree of complexity. The third stage consisted of incorporating these mechanistic models into a macro-scale model of the PSD. Using novel experimental design techniques, the relative importance of the different factors on the PSD, and the aspects of the model that needed refinement were determined. The final stage consisted of implementing changes to the model in a balanced and effective way. The result was an improved model for PSD that assigns adequate weight to the importance of each key factor, with similar degree of complexity as the best models reported in the literature, but better performance and increased reliability of predictions. Some of the contributions of this thesis to the field of Polymer Science and Engineering include: the development and validation of an effective model for crosslinking free-radical copolymerization kinetics; the establishment of prescriptions to guide the efforts in the acquisition and interpretation of information aimed at improving our understanding and modelling capabilities of suspension polymerization reactors; the inclusion, for the first time in suspension polymerization modelling, of non-homogenous mixing in the stirred tank reactor into the PSD model; the development of mathematical models for breakage and coalescence in liquid-liquid dispersions, and the systematic and effective use of mechanistic modelling for experimental design purposes in polymer production studies.
Keywords: Chemical Engineering; Chemical Engineering